Integrating Computer Technology in Education: From Traditional Pedagogy to E-Learning Transformation: https://doi.org/10.5281/zenodo.17406386 - Tanvir Ahmed; Rai Samee Ullah; Dr. Sadaqut Ali; Ishfaq Ali (`, 2025)
Computers have revolutionized modern education by transforming traditional teaching and learning paradigms into dynamic, technology-driven systems. Initially developed for computation, computers now serve as powerful tools for interactive learning, knowledge management, and educational accessibility. Their integration into classrooms and virtual environments supports individualized instruction, encourages active learning, and facilitates efficient information storage and retrieval. This paper explores the multifaceted role of computers across instructional, revelatory, conjectural, and emancipatory learning paradigms, emphasizing their contribution to education, training, and indoctrination processes. Furthermore, it discusses the evolution of computer-assisted and computer-managed learning models, the emergence of E-Learning frameworks, and the challenges within existing educational systems rooted in traditional structures. By analyzing the pedagogical and technological dimensions of computer-based education, this study highlights the transformative potential of digital tools in achieving learner autonomy, expanding access, and promoting continuous knowledge innovation. Key Words: Computer-assisted learning, E-Learning, Computer-managed instruction, Educational technology, Training, Curriculum development